Making Memory (in) Concrete. A Material Perspective - Rava, Gabriella (E|C, 2023)
The inspiration for reflecting on the historical time embodied by concrete comes from two episodes from Grass’ The Tin Drum (1959) which take place among the bunkers of the Atlantic Wall. The relation that Grass establishes between these concrete buildings and the History to come seems to reverse the general perception of this material as almost unhistorical (Forty 2005, 2012), ultimately unable to convey a temporality of the past. The “unexpected” connection between concrete and memory/history is then further investigated through two case studies, that of the Brion Tomb realized by Carlo Scarpa and the so-called concrete punishment (Delso 2018), i.e., the practice of pouring concrete into the houses of Palestinian attackers deployed by the Israeli military. Regarded as examples of the “misuse” of concrete, they show that this material is able to convey different conceptions of memory that may eventually “rediscover” the irreducible matter (Bennett 2010) behind the material, never fully determined by human agency.